Penerapan Media Pembelajaran 3D Berbasis Aplikasi Assemblr Edu untuk Meningkatkan Minat Belajar Siswa dalam Pembelajaran Geografi - Suci Maulidita; Momon Dt Tanamir; Trina Febriani (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to find out and identify the feasibility, practicality, and interest of students in using 3D learning media based on the assemblr edu application in the subject of Geography in class X SMAN 2 Kota Solok. The type of research used in this research is action research. The subjects of this research trial were students in grades XE7 and XE10 for the 2022/2023 school year, a total of 71 students. The results of this study are: (1) 3D learning media can be declared very feasible after conducting tests with a total score of 140 with a mean of 4.65 and a percentage level of 93% with the title